2022
DOI: 10.1007/s13346-022-01172-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycerosomal thermosensitive in situ gel of duloxetine HCl as a novel nanoplatform for rectal delivery: in vitro optimization and in vivo appraisal

Abstract: Duloxetine HCl (DXH) is a reuptake inhibitor of serotonin and norepinephrine used to treat the major depressive disorder. Following its extensive hepatic metabolism, acid-labile nature, and limited aqueous solubility, DXH has poor oral bioavailability (40%). The rectal route has been suggested as another route of administration to surmount such challenges. The present study aimed to prepare DXH-loaded glycerosomal (DXH-GLYS) in situ gel for rectal administration to increase DXH permeability and improve its bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Nanotechnology is defined as the manipulation of materials at the nanoscale (Salem et al., 2022 ). Numerous nations and significant organizations have become interested in investing in the rapidly emerging industry of nanotechnology research (Ali et al., 2021 ; Hussein et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanotechnology is defined as the manipulation of materials at the nanoscale (Salem et al., 2022 ). Numerous nations and significant organizations have become interested in investing in the rapidly emerging industry of nanotechnology research (Ali et al., 2021 ; Hussein et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous nations and significant organizations have become interested in investing in the rapidly emerging industry of nanotechnology research (Ali et al., 2021 ; Hussein et al., 2022 ). Nanoscale materials have previously unheard-of physical, chemical, and biological properties that could enhance or change the characteristics of drugs (Alhakamy et al., 2022 ; Salem et al., 2022 ). For the improvement of features of medications such as solubility and stability, successive delivery paradigms called nanoemulsions (NEs) are useful (Rizg et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into nanotechnology caught the attention of researchers in several countries and large corporations and led to investments in the field, which developed swiftly ( Ali et al, 2021 ; Hussein et al, 2022 ). Nanosized materials have unprecedented physical, chemical, and biological merits and may improve or alter drug characters ( Alhakamy et al, 2022 ; Salem et al, 2022a ). Nanoemulsions (NEs) are progressive delivery paradigms that are convenient for boosting drug properties such as solubility and stability ( Rizg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Duloxetine hydrochloride (DUL; (3 S )- N -methyl-3-naphthalen-1-yloxy-3-thiophen-2ylpropan-1-amine) is considered a novel antidepressant drug acting via a dual mechanism, being selective serotonin as well as norepinephrine reuptake inhibitor ( Salem et al, 2022 ). It was reported that DUL shows higher potency, more efficacy, and less toxicity compared to other antidepressant drugs ( Khatoon et al, 2019 ; Setia et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that DUL shows higher potency, more efficacy, and less toxicity compared to other antidepressant drugs ( Khatoon et al, 2019 ; Setia et al, 2013 ). Although DUL shows high oral absorption ( Elsenosy et al, 2020 ), variable poor bioavailability (≈ 40%) is achieved due to the extensive degradation in the acidic medium of the gastrointestinal tract and first-pass metabolism via the hepatic cytochrome P450 P1A2 ( El Sharawy et al, 2017 ; Salem et al, 2022 ). DUL, a BCS class-II drug, is considered a promising candidate for intranasal, as well as transdermal drug delivery, due to its physicochemical properties including lipophilicity (log P = 4.2) and molecular weight (330 g/mol) ( Peddapalli et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%